Benzamide Derivatives Targeting the Cell Division Protein FtsZ: Modifications of the Linker and the Benzodioxane Scaffold and Their Effects on Antimicrobial Activity - Valentina Straniero; Lorenzo Suigo; Andrea Casiraghi; Victor Sebastián-Pérez; Martina Hrast; Carlo Zanotto; Irena Zdovc; Carlo De Giuli Morghen; Antonia Radaelli; Ermanno Valoti (MDPI AG, 2020)
Filamentous temperature-sensitive Z (FtsZ) is a prokaryotic protein with an essential role in the bacterial cell division process. It is widely conserved and expressed in both Gram-positive and Gram-negative strains. In the last decade, several research groups have pointed out molecules able to target FtsZ in Staphylococcus aureus, Bacillus subtilis and other Gram-positive strains, with sub-micromolar Minimum Inhibitory Concentrations (MICs). Conversely, no promising derivatives active on Gram-negatives have been found up to now. Here, we report our results on a class of benzamide compounds, which showed comparable inhibitory activities on both S. aureus and Escherichia coli FtsZ, even though they proved to be substrates of E. coli efflux pump AcrAB, thus affecting the antimicrobial activity. These surprising results confirmed how a single molecule can target both species while maintaining potent antimicrobial activity. A further computational study helped us decipher the structural features necessary for broad spectrum activity and assess the drug-like profile and the on-target activity of this family of compounds.